Studi Kritik Hadis Tentang Mengkonsumsi Hewan Hasil Buruan dari Anjing Yang Terlatih - Munadi, Radhie (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2023)
Hunted animals are closely related to food. The body needs food to live to allow the body to function normally. On the other hand, some people deliberately hunt animals using tools such as rifles, game animals or other media. This is what requires deeper study regarding the phenomenon that occurs in the community about hunting animals or fauna with other game animals. The question is how far is the quality of the hadith about exploiting fauna by eating the prey of trained dogs? And how does the analysis of sanad and matan regarding the hadith consume animals caught by trained dogs. In this study, the process of takhrij al-hadith was carried out using the takhrij method. In order to issue and find hadiths related to the discussion, a sanad and matan criticism was carried out to ensure the validity of the hadith. After the research, it was found that the sanad in the hadith under study is valid as well as the matan of the object of study of the hadith is also valid, so it can be concluded that this hadith has valid validity.